PEMENUHAN HAK DAN KEWAJIBAN SEBAGAI ORANG TUA PENYANDANG DISTABILITAS - Dwi Puspita, Della Ayu (Samawa (Sakinah, Mawaddah Warahmah), 2025)
This article examines Islamic legal perspectives on fulfilling rights and obligations of parents with disabilities in performing childcare. The study uses a normative–sociological approach to analyze Islamic legal principles, maqasid al-sharia, Indonesian disability regulations, and empirical realities of disabled parenting. The findings indicate that Islamic law upholds equality and does not discriminate based on disabilities. Parenting rights remain valid as long as parents demonstrate functional capacity to protect and nurture the child. Furthermore, Islamic and national legal frameworks align in emphasizing the best interests of the child as the core determinant of custody. Social stigma, structural barriers, and limited accessibility remain the primary challenges for parents with disabilities. This study argues that a more inclusive social environment and state support are necessary to ensure that Islamic justice values are implemented in real contexts